Ecologically considered design of operational systems for high-rise buildings in Kolkata - Chakraborty, Kalyan (Kansas State University, 2010)
This thesis presents design possibilities for reducing the ecological impact of the operational systems of high-rise buildings in Kolkata, India. This research is supported by a study of the current urban situation of Kolkata which shows a recent growth in number of high-rise buildings and a need for ecological considerations in their operational systems. To fulfill this need this thesis studied recent developments in alternative operational system design and explored the possibility of developing operational systems in a proposed residential high-rise building. In the process of developing an alternative operational system for a high-rise building in Kolkata this thesis firstly studied development of operational systems in high-rise buildings and recent sustainable architectural guidelines to understand the primary design necessities for ecological considerations. Secondly a study of alternative design strategies and techniques was done and a research for the development of a building integrated solar thermal updraft façade was carried out. The research into a building integrated solar thermal updraft façade showed the possibility of developing a façade system in high-rise buildings which can generate electricity. Finally on the basis of the studies and the research an analysis was done to check the reduction in carbon footprint and improvement in the design of operational systems in a hypothetical high-rise residential building in Kolkata.
Keywords: Sustainable high-rise; High-rise farming; Operational systems; Solar updraft double skin fadace; Living machine; High-rise power generation; Architecture (0729)